Pengaruh Kualitas Produk terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Variabel Intervening pada Konsumen Hanasui di Toko Citra Cosmetic Boulevard - Arnita Nuranita Mudir; Muhammad Ichwan Musa; Muhammad Ilham Wardhana Haeruddin; Isma Azis Riu; Nurul Fadilah Aswar (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
Indonesia in 1997-1998. The main factor that caused the crisis was the government's widening of the economy, in which the government made concessions to borrow debt without strict supervision and selection. As a result, many businessmen were unable to pay their debts on time, so that Indonesia's reputation declined internationally. Islamic ethics is a branch of philosophy that is critical and rational which investigates good and bad and human obligations. Islam as a comprehensive and universal religion regulates all aspects of human life including in the field of trade or commerce business. In the field of worship, Islam stipulates the law "there is no worship except what is regulated in the Al-Quran and Sunnah" while for jnn muamalah activities it only regulates the principles. Business Ethics in an Islamic perspective focuses on principles that do not conflict with the Al-Quran and Sunnah and provide justice and benefit for all parties involved in the business process